Students’ of Teacher Profession Education Problem Solving Ability in Implementing Mathematics Learning in Plane Geometry - Riva Widyastuty; Cut Morina Zubainur (Proceedings of AICS - Social Sciences, 2019)
One of the efforts made by the Government to improve teachers’ quality and professionalism is through Teacher Profession Education (TPE). TPE’s student as prospective professionals are required to have problem solving skills. However, there is no information about teacher’s problem solving skills when attending TPE’s program. In fact, problem solving ability is one of the skills that students must have to face the challenges of time. This study aimed to describe TPE’s students problem solving ability in implementing mathematics learning in plane geometry in Junior High School. The subjects are two students’ of TPE who are TPE in Junior High School. The data collection techniques in this research are observation, documentation, and interview. Based on the research result, problem solving skill for subject 1 about plane geometry satisfied the problem solving skill indicator with maximum score, in the other hand problem solving skill for subject 2 was not meet the problem solving skill indicator, it could be indicated from the problem solving skill for subject 2 that almost got minimum score in each indicators. Implications are drawn regarding the teaching of geometry and the problem solving ability of TPE's student.